Greenfield and Brownfield Investments and Economic Growth: Evidence from Central and Eastern European Union Countries - Bayar, Yilmaz (Naše gospodarstvo/Our economy, 2017)
Global foreign direct investment flows in terms of greenfield and brownfield investments have increased during the recent three decades resulting from the accelerating globalization. The considerable increases in the flows of foreign direct investment have many eventualities for the national economies. This study investigates the mutual effects among greenfield and brownfield (mergers and acquisitions) investments and economic growth in Central and Eastern European Union countries during the 2003–2015 period employing panel data analysis. The findings revealed that both greenfield and brownfield investments had positive influence on the economic growth, but the influence of greenfield investments was found to be relatively higher. Furthermore, one-way causality was discovered from both greenfield and brownfield investments to the economic growth.